Determinan Profitabilitas Dengan Pembiayaan Bagi Hasil Sebagai Variabel Intervening Pada Bank Umum Syariah - Laili, Yasfillahul; Bawono, Anton (Mandiri : Jurnal Akuntansi dan Keuangan, 2022)
The purpose of this study is to determine the influence of Third Party Funds (DPK), Revenue Sharing Rate, Non-Performance Financing (NPF), SBIS on Profitability with Profit Sharing Financing as Intervening Variables at Sharia Commercial Banks in Indonesia with a research period from 2014-2020. The data used in this study is secondary data. The data in this study was obtained from the financial statements of Sharia Commercial Banks. (BUS), both published by each website of Sharia Commercial Banks and published by Bank Indonesia. Samples were taken as many as 9 Sharia Commercial Banks. Data retrieval techniques by purposive sampling. The data obtained is then processed using Eviews tools. This study uses a type of quantitative research using multiple regression analysis and Path Analysis as data analysis.The results of this study showed that DPK and NPF variables have a negative and significant effect on the profitability of Sharia Banks. Profit-sharing, SBIS, and Profit-Sharing Financing have a positive and significant impact on the Profitability of Sharia Banks. DPK has a positive and insignificant effect on Sharia Bank Revenue Sharing Financing. NPF variables negatively and significantly affect Sharia Bank Revenue Sharing Financing. Variable Revenue Sharing Rate and SBIS negatively and significantly affect Profit Sharing Financing. The Path Analysis test showed that Revenue Sharing Financing can mediate the influence of Revenue Sharing Level, NPF, and SBIS on Sharia Bank Profitability. However, Profit Sharing Financing cannot mediate the influence of deposits on sharia bank profitability